Stress Analysis of High-Pressure Steam Header Manifold from Power Boiler to Distribution System Piping Using The Caesar II Software - Kurniawan, Wanda; Rahmawaty, Made (Jurnal IPTEK, 2023)
In the construction of the oleochemical plant project, there is a steam pipe that experiences excessive stress during the stress analysis phase using stress analysis software. The pipe is connected to either a boiler or a steam generator equipment. Recalculation is necessary, including for the allowable pipe span and pipe flexibility, to address the excessive stress. The pipe falls into the category of critical pipe, thus requiring stress analysis after the recalculation is performed. The stress analysis is conducted using sustained load, occasional load, and thermal load based on ASME B31.3. The calculation of the allowable pipe span takes the smallest value between the minimum distance based on stress limit and deflection limit, which is 19,006 ft, and the minimum required number of supports, which is 22. The results of the calculation for the allowable pipe span are acceptable as the number of supports meets the minimum required amount. The flexibility calculation yields a value smaller than K1, specifically 0.000916, indicating that the pipe is declared flexible. The highest stress value at node 688 for sustained load is 18,389.3 psi, and the highest value at node 688 for occasional load, it is 18,399 psi. The highest stress value for thermal load, 1420.6 psi, is found at node 168. The stress values for all three load cases do not exceed the allowable stresses. Therefore, the design is declared safe during operation